Concurrent shifts in wintering distribution and phenology in migratory swans ... - Nuijten, Rascha; Wood, Kevin; Rees, Eileen; Nolet, Bart (Dryad, 2020)
Range shifts and phenological change are two processes by which organisms respond to environmental warming. Understanding the mechanisms that drive these changes is key for optimal conservation and management. Here we study both processes in the migratory Bewick’s swan (Cygnus columbianus bewickii) using different methods, analysing nearly 50 years of resighting data (1970-2017). In this period the wintering area of the Bewick’s swans shifted eastwards (“short-stopping”) at a rate of >12.5 km y-1, thereby shortening individual migration distance on average by 353 km. Concurrently, the time spent at the wintering grounds has reduced (“short-staying”) by ~38 days since 1989. We show that individuals are consistent in their migratory timing in winter, indicating that the frequency of individuals with different migratory schedules has changed over time (a generational shift). In contrast, for short-stopping we found evidence for both individual plasticity (individuals decrease their migration distances over ... : Data has been collected by a >50 year ring-resighting project of both legrings (1970-present) and neckbands (1989-present). ...